2018
DOI: 10.1108/jhlscm-07-2017-0036
|View full text |Cite
|
Sign up to set email alerts
|

Resource selection in support of humanitarian operations: a case of the United States Navy

Abstract: Purpose The purpose of this paper is to present a model for selecting specific assets to be used in relief and disaster response missions based on the capabilities of, and contributions to, the demanded need for humanitarian assistance and disaster relief. During past disasters, the US Navy (USN) has responded with whatever ships were in the area regardless of their contribution to the need. The authors use data from the USN that has been gathered in other studies as an illustration of how the model may be app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Apte and Yoho (2017) further elaborate on the costs of the humanitarian operations, indicating that vertical lift is one of the most expensive capabilities for the USN. Combining the findings of these two articles, Apte and Yoho (2018) offer an optimization model that incorporates two of the attributes, capability and cost of USN ships. In this research, we push the research further to simultaneously incorporate capability, proximity to the disaster location, and cost.…”
Section: Literature Surveymentioning
confidence: 99%
“…Apte and Yoho (2017) further elaborate on the costs of the humanitarian operations, indicating that vertical lift is one of the most expensive capabilities for the USN. Combining the findings of these two articles, Apte and Yoho (2018) offer an optimization model that incorporates two of the attributes, capability and cost of USN ships. In this research, we push the research further to simultaneously incorporate capability, proximity to the disaster location, and cost.…”
Section: Literature Surveymentioning
confidence: 99%
“…Most of the research used a "capability scoring system" to grade ship types in terms of capabilities and competencies to support HADR. Apte and Yoho (2018) and Apte et al (2020) confirmed these results, emphasizing that ships with vertical lift capabilities are far more valuable than the ones that do not have that capability, in the performance of HADR missions. Baker et al (2002), Salmeron and Apte (2010), Mogilevsky (2013), Burgos and McLean (2018) and Scott and Watson (2018) utilize optimization modeling to resolve issues in air-transportation of supplies to disaster-stricken areas.…”
Section: Literature Reviewmentioning
confidence: 52%
“…Some of the literature finds out which ships in the Navy provide the most potential support to HADR and, perhaps more importantly, which ships do not (Kaczur et al, 2012;Apte et al, 2013Apte et al, , 2020Moffat, 2014;Apte and Yoho, 2018). Aurelio et al (2012) analyze the USN response to T ohoku earthquake in 2011.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations